Accuracy of whole genome sequencing versus phenotypic (MGIT) and commercial molecular tests for detection of drug-resistant Mycobacterium tuberculosis isolated from patients in Brazil and Mozambique. (May 2018) - Feliciano, Cinara Silva; Namburete, Evangelina Inacio; Rodrigues Plaça, Jéssica; Peronni, Kamila; Dippenaar, Anzaan; Warren, Robin Mark; Silva, Wilson Araújo; Bollela, Valdes Roberto
Abstract: Background: The fast and accurate diagnosis of drug-resistant tuberculosis (DR-TB) is critical to reducing the spread of disease. Although commercial genotypic drug-susceptibility tests (DST) are close to the goal, they are still not able to detect all relevant DR-TB related mutations. Whole genome sequencing (WGS) allows better comprehension of DR-TB with a great discriminatory power. We aimed to evaluate WGS in M. tuberculosis isolates compared with phenotypic and genotypic DST. Methods: This cross-sectional study evaluated 30 isolates from patients with detected DR-TB in Brazil and Mozambique. They were evaluated with phenotypic (MGIT-SIRE™) and genotypic (Xpert-MTB/RIF™, Genotype-MTBDRplus™, and MTBDRsl™) DST. Isolates with resistance to at least one first- or second-line drug were submitted to WGS and analyzed with TB profiler database. Results: WGS had the best performance among the genotypic DST, compared to the phenotypic test. There was a very good concordance with phenotypic DST for rifampicin and streptomycin (89.6%), isoniazid (96.5%) and ethambutol (82.7%). WGS sensitivity and specificity for detection resistance were respectively 87.5 and 92.3% for rifampicin; 95.6 and 100% for isoniazid; 85.7 and 93.3% for streptomycin while 100 and 77.2% for ethambutol. Two isolates from Mozambique showed a Val170Phe rpoB mutation which was neither detected by Xpert-MTB/RIF nor Genotype-MTBDRplus. Conclusion: WGS was able to provide all the relevant information about M. tuberculosis drug susceptibility in a single test and also detected a mutation in rpoB which is not covered by commercial genotypic DST.